Penyebutan Muwathin sebagai Strategi Inklusivitas Hukum dan Sosial di Indonesia: Telaah Praktis dan Yuridis atas Keputusan Konferensi Besar Nahdlatul Ulama Tahun 2019 - Imron Hamzah (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the practical and juridical consequences of the use of the term muwathin (citizen) in place of the term kafir in the context of Indonesian national law, as recommended in the 2019 Konbes Alim Ulama of Nahdlatul Ulama (NU). This term change is understood as a response to the need to strengthen equality, inclusiveness and tolerance in a multicultural society. This research uses a descriptive qualitative approach with normative and theoretical analyses through theories of multiculturalism, Rawlsian justice, legal pluralism, as well as communication theory and critical law. The results show that practically, the mention of muwathin encourages the recognition of equal rights and obligations for all citizens regardless of religion, removes theological stigma, strengthens unity, and changes public communication and policies to be more inclusive. Juridically, the term supports the principle of a just and non-discriminatory rule of law, encourages revision of legal language, and affirms the limits of authority of religious institutions in the national legal system. The discussion in this article links these changes to the dynamics of a modern plural and democratic nation state. The mention of muwathin is not just a semantic change, but a socio-political and legal strategy to strengthen the social contract and civic nationalism. The conclusion states that this step is strategic in strengthening the principles of justice, equality and harmonious national life, and is an important foothold for the development of an inclusive national law.